Why We Have to Develop Instruments of Our Caring Measurement Based on an Indonesian Perspective - Candra Panji Asmoro; Rr Tutik Sri Hariyati; Andri Setiya Wahyudi (Universitas Airlangga, 2020)
Introduction: Caring is the core or focus in nursing as a form of professional nursing practice. The current caring instrument is an original instrument that measures the attitudes or behavior of nurses, has not paid attention to the administrative and environmental aspects of the hospital. The use of an instrument that does not yet contain certain characteristics gives rise to improper measurement results. The purpose of this study was to explain the importance of developing caring measurement instruments with an Indonesian perspective. Methods: Systematic reviews were carried out from database articles on ScienceDirect, Scopus, Google Scholar, SpringerLink, Wiley online, Proquest, and EBSCOhost. Criteria for articles were articles published in the last 10 years, national and international research locations, and in Indonesian and English. 15 references were obtained from 2100 references that met the predetermined criteria. The development of a caring behavior instrument based on an Indonesian perspective does not yet exist. Results: The results found that development on the basis of linguistics, cultural adjustment, and according to the prevalence of disease in a country because the epidemiology of the disease differs on the climate region. Conclusion: Specific caring instruments in an Indonesian perspective is expected that the research results will be more accurate.